Implementasi Manajemen PTKIS Berbasis Pondok Pesantren (Studi di STISHK Kuningan) - Sehan Rifky; Ahmad Yani; Dewi Cahyani (UMSU, 2023)
This study presents the Management of Islamic Boarding School-based Higher Education, its advantages, and differences from non-Islamic boarding schools. The research subject in this paper is a private Islamic religious college (PTKIS) based on Islamic Boarding Schools in Kuningan Studies at the Husnul Khotimah College of Sharia Studies (STISHK). The data in this study were obtained through documentation, observation, and in-depth interviews. The results of this study are the implementation of management in Islamic boarding schools based tertiary institutions, an atmosphere that is maintained and supportive to create a scientific and Islamic environment and maximum learning patterns because students are in dormitories. Lecturers with at least masters and doctoral degrees graduated abroad and are in line with their majors. The system and policies adapt to the Islamic boarding schools as the main base, there is a full scholarship program where graduates are required to memorize 5 chapters of the Qur'an and be able to communicate using Arabic and English, have a strong tabawiyah spirit and can become da'wah cadres in society. Even though it is in a pesantren environment and has minimal access to outside schools, in this case pesantren-based tertiary institutions continue to make updates so that they can compete and not be left behind from non-Islamic boarding schools by conducting seminars that invite academics and professionals to attend and conduct comparative studies and collaboration. with various parties so that they are always supported and given the trust of the community.